(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This type of research is experimental research. This study aims to determine: 1) The effect of command training style on dribbling skills in SSB Syekh Yusuf students; 2) The effect of task training style on dribbling skills in SSB Syekh Yusuf students; and 3) The difference in the effect of command training style and task training style on dribbling skills in SSB Syekh Yusuf students. The population in this study were SSB Syekh Yusuf students with a sample used of 40 students with a sampling technique using and a group division system using maching ordinal pairing. The results of the study showed that; (1) There is an influence of the command training style on dribbling skills in Syekh Yusuf SSB students aged 13-15 years, as evidenced by an increase in speed from an average value of 21.3230 to 119.4310 with an observation value of 9.124 > ttable 2.262 and a significant value of 0.000 < α0.05, while the command training style for 10-12 year olds is evidenced by an increase in speed from an average value of 23.7720 to 18.9960 with an observation value of 11.605 > ttable 2.262 and a significant value of 0.000 < α0.05. (2) There is an influence of the task training style on dribbling skills in Syekh Yusuf SSB students aged 13-15 years, as evidenced by an increase in speed from an average value of 21.4390 to 17.0840 with an observation value of 10.545 > ttable 2.262 and a significant value of 0.000 < α0.05; while the task training style for 10-12 year olds is evidenced by an increase in speed from an average value of 23.8130 to 21.0560 with an observation value of 9.093 > ttable 2.262 and a significant value of 0.000 < α0.05. (3) There is a difference in the influence between the command training style and the task training style on dribbling skills in SSB Syekh Yusuf students aged 13-15 years with a difference value of 19.4310 > 17.0840 with an observation value of 4.309 > ttable 2.101 and a significant value of 0.000 < α0.05. While the difference in the influence of the command training style and task training for ages 10-12 with a difference value of 18.9960 < 21.0560 with an observation value of 4.396 > ttable 2.101 and a significant value of 0.000 < α0.05. The conclusion is that the command training style for ages 13-15 years both have the same influence, and the task training style is better than the command training style. While for ages 10-12 years, the command training style is better than the task training style on dribbling skills in SSB Syekh Yusuf students.